Model Arsitektur Akar Lateral dan Akar Tunjang Bakau (Rhizophora apiculata Blume.) - Zulkifli Dahlan; Sarno Sarno; Afif Barokah (Faculty of Mathtmatics and Natural Sciences, 2009)
The research about architectural model of lateral and stilt root of Bakau (Rhizophora apiculata Blume.) was conducted on August 2008 at Inwrought Management Area of Mangrove Forest, Margasari, Labuhan Maringgai Sub-District, East Lampung Regency, Province of East Lampung. This research aim to analyze the model of root architecture or the R. apiculata at different growth phases. The approach used the survey descriptive method (qualitative and quantitative). This research is conducted directly in field to get the data of lateral root architecture (underground system) and stilt root by using method of profile root trenching. The result showed that the lateral root at 1, 2, and 4 years old measure up to the monopodial with the orientation of axes is orthotropic and plagiotropic (syllepsis), while the stilt root at 12 years old measure up to the monopodial pattern with the orientation of axes is orthotropic branch complex (non-terminalia branching). Characteristic of R. apiculata root growth is continuous. It was concluded that the architectural model of R. apiculata root is combination between Troll’s and Champagnat’s model.